An Analysis of PT Bank OCBC NISP Tbk’s Strategic Responses to Challenges in Indonesia’s Banking Industry - Febrian Aldi Prasetyo; Nella Manda Maryana; Lutfi Fadilah; Harti Budi Yanti (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2026)
This research uses descriptive qualitative analysis methods to identify the strategy of PT Bank OCBC NISP Tbk (rebranded as OCBC Indonesia in November 2023) in facing challenges in the Indonesian banking industry. By using analysis based on the Triple Bottom Line (TBL) approach and the Dynamic Capabilities Framework (DCF), this research explores the steps taken by OCBC Indonesia to maintain its position amidst intense competition, both from conventional and digital banks. The research results show that OCBC Indonesia faces various challenges, such as competition from fintech, regulatory changes, and demands to integrate sustainability principles (ESG). In responding to these challenges, OCBC Indonesia strengthens its Sensing and Seizing Capabilities under the DCF through the development of digital services such as the ONe Mobile application and investment in innovative technologies such as big data and AI-powered risk management systems, while simultaneously expanding sustainability-based products such as green loans as a concrete manifestation of the Environmental pillar within the Triple Bottom Line framework. This strategy allows OCBC Indonesia to increase operational efficiency, attract the interest of investors who care about sustainability, and meet the needs of customers who are increasingly environmentally conscious.